Understanding hope from the voices of service users and providers across Canada - Cristina Alexandra Guerrero; Tina Lackner (Journal of Innovation in Polytechnic Education)
Although Canada is home to the second largest non-profit and volunteer sector in the world, there is an absence of an overarching framework to guide human services delivery (Hall et. al., 2005; Rahmani, 2022). This paper documents the first phase of a three-year study that seeks to begin to bridge this gap by learning from both HS providers and users’ narratives, specifically in relation to the topics of hope, self-compassion, and authentic collaboration.